10-3x=2x-8x+40
10-3x=-6x+40
10+3x=40
3x=30
x=10
:)
2006-11-07 14:00:32
·
answer #1
·
answered by Jovigrl 2
·
0⤊
0⤋
x = 10
2006-11-07 14:04:59
·
answer #2
·
answered by Kobby B 1
·
0⤊
0⤋
x = 10
2006-11-07 13:59:36
·
answer #3
·
answered by s w 4
·
0⤊
0⤋
x=10
2006-11-07 14:08:15
·
answer #4
·
answered by 7
·
0⤊
0⤋
10- 3x = 2x - 8x + 40
take all like terms on one side
-3x - 2x + 8x = 40 - 10
+ 3x = 30
x = 30 / 3
x = 10
2006-11-07 14:03:21
·
answer #5
·
answered by Muskaan 1
·
0⤊
0⤋
10-3x=2x-8x+40
so first, look at both sides and combine like terms.
the left side has no like terms so for now, leave it alone.
the right side, on the other hand, has 2x-8x, so we can combine this to be -6x
our new equation looks like this:
10-3x=-6x+40
now, add the -6x to both sides, so it cancels on the right side, and it adds to the left side to produce the following:
10-3x=40
now, subtract 10 from either side, which will result in 0 on the left side and 30 on the right to give you:
-3x=30
now, divide both sides by -3, so you have an equation that is "x="
x=30/-3
now, simplify the equation to
x=-10
this is your answer, in a long-winded, step-by-step manner....you'll be fine if you can just remember to combine like terms before evaluating the rest of the problem.
2006-11-07 14:53:45
·
answer #6
·
answered by Christie 3
·
0⤊
0⤋
Sure, this is pretty simple
10 - 3x = 2x - 8x + 40
10 - 3x = -6x + 40
-3x = -6x + 40 - 10
-3x = -6x + 30
-3x + 6x = 30
3x = 30
x = 30/3
x = 10
I hope that helped
2006-11-08 02:27:01
·
answer #7
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
first get all like terms on same side;
10-40=2X-8X+3X
or
2x+3x-8x=-30
5x-8x= -30
-3x= -30
multiply both sides by -1
3x=30
divide both sides by 3
x=10
if ya want plug 10 into orginal equation and the result shoud cancel out
2006-11-07 14:03:15
·
answer #8
·
answered by ontopofoldsmokie 6
·
0⤊
0⤋
= 10 - 3x = -6x + 50 (then add 6x to each side)
=10 + 3x = 50 (then subtract 10 from each side)
= 3x = 40
= x = 40/3 or 13.333333
2006-11-07 14:04:00
·
answer #9
·
answered by ryan_demeter 2
·
0⤊
0⤋
10 - 3x = 2x - 8x + 40
-3x - 2x + 8x = 40 - 10
3x = 30
x = 10
2006-11-07 14:10:30
·
answer #10
·
answered by kezongputi 2
·
0⤊
0⤋